Towards privacy monitoring based on information tracking for Android - Chia, Ruella Xin Yi (2014)
The proliferation of smartphone ownership and use has raised privacy concerns on mobile platforms. With the increasing capability of smartphones, users are relying more on them to store and handle personal data – most of which are sensitive information. The work done in this project involves different parts of the information tracking system. Sensitive information to be detected was first defined, and an Android app, DroidHttpDebugger was created to capture HTTP traces and detect the leak of sensitive information. Although there can be many ways of detecting sensitive information leak, the approach adopted in the project is through real-time monitoring. The main component in the app will capture HTTP traffic using a proxy server, which acts as an intermediary between the requesting app and the web server. The app also allows for users to create a manual HTTP request, and users can use the app to view the information being exchanged between the app and the web server. In addition to developing an Android app, HTTP traces were manually collected from different versions of popular apps with the app Catlog for additional analysis and some methods were implemented in the tool CLTK to verify if a given string from pre-processed traces is sensitive.